EFFECTS OF TRANSITIONAL CARE PROGRAM FOR STROKE PATIENTS ON FAMILY CAREGIVER’S READINESS AND BURDEN - Kimhong, Pasika; Wattradul, Duangkamol; Chutinet , Aurauma (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
This quasi-experimental research aimed to study the effects of the transitional care program for stroke patients on family caregivers’ readiness and burden. The sample consisted of family caregivers of stroke patients admitted to King Chulalongkorn Memorial Hospital, the Thai Red Cross Society. Purposive sampling was used to select subjects. The control group (n = 28) received routine nursing care, while the experimental group (n = 28) received routine nursing care along with the transitional care program for seven consecutive days during hospitalization, followed by six weeks of continuous follow-up phone visits after discharge. Caregivers were provided with teaching material through the LINE official account, consisting of video clips and five infographics. Data were collected using questionnaires for the family caregiver’s readiness, and the family caregiver’s burden. Descriptive statistics, Chi-square tests, and t-tests were employed for data analysis. The results revealed that the mean score of family caregivers’ readiness after the experiment in the experimental group was significantly higher than that of the control group (t = -14.00, p = .00). Additionally, the mean score of family caregivers’ readiness after the experiment in the experimental group was significantly higher than that before the experiment (t = -29.86, p = .00). Moreover, the mean score of family caregivers’ burden after the experiment in the experimental group was significantly lower than that of the control group (t = 12.32, p = .00), and lower than that before the experiment (t = 26.38, p = .00). Therefore, nurses are encouraged to utilize the transitional care program and the LINE official account to enhance the readiness of stroke patients’ family caregivers.